2020
DOI: 10.5539/jas.v12n11p1
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Potential of Hesperozygis ringens Extracts on Seed Germination of Soybeans and Beggarticks

Abstract: Hesperozygis ringens L., popularly known as espanta-pulga, is a native shrub found in rocky fields in Rio Grande do Sul. Its leaves produce a lot of essential oil, which contains pulegone as a main component that may be allelopathic. The objectives of this study were to analyze the allelopathic effects of H. ringens leaf extracts on the germination and initial development of soybean seeds and to evaluate the herbicidal potential of these extracts on beggarticks (Bidens pilosa L.). The seeds were placed on pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…To carry out the experiments, the leaves of Manihot esculenta collected in the afternoon were initially dried in an oven and ground in a blender for approximately 2 minutes at the rate of 10 g of dry leaves to 100 mL of distilled water, which was considered the 100% (p/v) crude extract, adapted from Lima et al (2020). The mixture remained at rest for 24 hours (in the dark and refrigerated at 5 ºC) and was then filtered through filter paper.…”
Section: Methodsmentioning
confidence: 99%
“…To carry out the experiments, the leaves of Manihot esculenta collected in the afternoon were initially dried in an oven and ground in a blender for approximately 2 minutes at the rate of 10 g of dry leaves to 100 mL of distilled water, which was considered the 100% (p/v) crude extract, adapted from Lima et al (2020). The mixture remained at rest for 24 hours (in the dark and refrigerated at 5 ºC) and was then filtered through filter paper.…”
Section: Methodsmentioning
confidence: 99%
“…For Hesperozygis ringens, some studies describe a high production of essential oil by the leaves, with pulegone (95.18%) as the principal component (Silva et al, 2014). The essential oil of this species has high antioxidant (Dolwitsch et al, 2020), antiparasitic and antimicrobial (Bandeira et al, 2017), alellopathic (Pinheiro et al, 2016;Lima, Lima, Birck, & Stefanello, 2020), and anesthetic and larvicide action (Silva et al, 2014). Additionally, in a pioneering work about in vitro cytotoxicity and genotoxicity, Dolwitsch et al (2020) demonstrated that its UAE-EtOH and SFE-CO 2 extracts are safe for human lymphocytes at the concentrations evaluated.…”
Section: Introductionmentioning
confidence: 99%